KEBEBASAN MEDIA MASSA DAN TANTANGAN INFODEMIK DI ERA DIGITAL: DINAMIKA, POLARISASI, DAN IMPLIKASI REGULASI - Nia Rahmi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
The rapid advancement of digital technology and the internet has fundamentally transformed the dynamic relationship between mass media and society. While this phenomenon expands the space for freedom of expression, it simultaneously introduces new challenges, such as the infodemic, the spread of disinformation, and information polarization driven by social media algorithms. This study aims to analyze the impact of digital technology on media freedom, identify the challenges mass media face in maintaining information integrity, and outline the regulatory roles of the government and relevant institutions in fostering a balanced information ecosystem. A descriptive-analytic qualitative method was employed, utilizing a literature review and content analysis of various scientific documents and regulatory frameworks. The findings indicate that digital transformation has shifted society’s role from passive consumers to content prosumers, requiring traditional media to adapt through participatory journalism, rigorous verification, and collaboration with factchecking organizations. Flexible regulations, enhanced public media literacy, and independent oversight by institutions such as the Press Council and KPI are vital. In conclusion, media freedom in the digital age must be balanced with social responsibility through synergy among the government, media, and the public to sustain democratic stability and ensure a healthy public sphere.